Efektivitas Penggunaan Aplikasi Zoom Cloud Meeting Sebagai Media Dakwah pada Masa Pandemi Covid-19 di Kajian Islam Center - Oktariani, Nadia; Lisnawati , Santi; Kosim, Ahmad Mulyadi (Indonesian Research Journal on Education, 2023)
The Covid-19 virus has had a major impact on all Indonesian people, requiring all people to keeptheir distance when meeting other people so they don't congregate, because otherwise it will produce new clusters in the spread of the Covid-19 virus. The teaching and learning process isdefinitely disrupted because it cannot be done in schools or campuses, as well as da'wah whichcannot be done in the assembly because it can collect prohibited mass. With the media as a means of communication that is quite effective for the community, it is located between two parties as intermediaries or supporters to function as a center for information retrieval. This research wasconducted to determine how effective the use of the Zoom Cloud Meeting application as a propaganda medium during the pandemic, to determine the supporting and inhibiting factors for the application. The type of research used is qualitative research. The type of research approach used is descriptive. The informants in this study were members of the Islamic Studies Center with 39 respondents. The data collection techniques in data collection are non-participant observation and structured interviews and documentation. Based on the results of the study, the use of the Zoom Cloud Meeting application as a propaganda medium was effective because it had a wide range, adequate electronic devices and quite efficient time.